Implementasi Pembelajaran PKn Berbasis Nilai-nilai Pancasila dalam Meningkatkan Sikap Toleransi Siswa Kelas V UPT SD Negeri 064016 - Anisa Wildayanty Harahap; Febrianti Putri Siahaan; Khairunnisa Khairunnisa; Yora Marsia Br. S Pandia; Syahrial Syahrial (International Forum of Researchers and Lecturers, 2025)
This study examines the implementation of Pancasila values-based Civic Education (PKn) learning in enhancing tolerance attitudes among fifth-grade students at UPT SD Negeri 064016. Using a descriptive qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews, document analysis, and tolerance attitude questionnaires involving 28 students. Results indicate that contextual strategies—such as classroom deliberation simulations and collaborative projects based on local wisdom—significantly improved students' tolerance attitudes. Conceptual understanding of diversity increased by 34.5%, empathetic attitudes rose by 29.5%, and inclusive practices grew by 23.7% (composite score +29%, Cohen’s d = 1.45). Key supporting factors included the school’s commitment to integrating Pancasila values into the curriculum and innovative media (e.g., multicultural congklak, AR cultural maps). Primary constraints were limited instructional time and student ability heterogeneity. The study concludes that Pancasila values-based learning models, supported by teacher consistency and active student participation, effectively foster inclusive school environments.